Membangun Loyalitas Karyawan dalam Era Persaingan Bisnis - Marlinawati Waruwu; Ray Octafian (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Employee loyalty is a strategic asset that determines an organization's long-term success in facing increasingly intense business competition. This study aims to identify the factors influencing employee loyalty, analyze its impact on organizational performance, and formulate effective and sustainable strategies for improving loyalty. The research adopts a descriptive-exploratory qualitative approach, involving 14 informants. Data collection was conducted through in-depth interviews, participatory observation, and document studies. Data analysis used a manual thematic analysis technique with a constant comparative approach and data triangulation to enhance the validity of the findings. The results show that employee loyalty at PT Sumber Bintang Rejeki is influenced by three main categories of factors. Organizational factors include an underdeveloped organizational culture with inconsistent implementation of values across departments, a human resource management system that needs improvement particularly in compensation and career development and diverse leadership styles that create inconsistencies in employee experience. Individual factors show that employees with longer tenure tend to have higher loyalty, while demographic characteristics such as gender and age influence loyalty perspectives in different ways. Work environment factors include physical conditions that need improvement, especially in the production department, and varying quality of interpersonal relationships across departments, with horizontal communication still being a challenge. The implementation of strategies is carried out through a comprehensive monitoring and evaluation system using a combination of quantitative indicators such as turnover rate and satisfaction surveys, as well as qualitative indicators through regular focus group discussions.